A Simplified Method for Preparing I131-Labelled Hippuran - Mitta, Aldo Eduardo Antonio; Fraga, Amanda; Veall, N. (Northern Ireland, 1961)
Fil: Mitta, Aldo Eduardo antonio Comisión Nacional de Energía Atómica; Argentina